2022
DOI: 10.1001/jamanetworkopen.2021.40196
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Home Time and Its Association With Quality of Life After Inpatient Surgery Among US Veterans

Abstract: IMPORTANCE Home time, defined as time spent at home after hospital discharge, is emerging as a novel, patient-oriented outcome in stroke recovery and end-of-life care. Longer home time is associated with lower mortality and higher patient satisfaction. However, a knowledge gap exists in the measurement and understanding of home time in the population undergoing surgery.OBJECTIVES To examine the association between postoperative home time and quality of life (QoL), functional status, and decisional regret and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Recent studies have also shown that home time after surgery is significantly correlated with quality of life, functional status, and emotional and social recovery. 17 Overall, these observations highlight the utility of home time as a hospital performance metric that captures meaningful differences in outcomes and patient-centered measures of care quality.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Recent studies have also shown that home time after surgery is significantly correlated with quality of life, functional status, and emotional and social recovery. 17 Overall, these observations highlight the utility of home time as a hospital performance metric that captures meaningful differences in outcomes and patient-centered measures of care quality.…”
Section: Discussionmentioning
confidence: 86%
“…[14][15][16] At the patient level, greater home time after inpatient surgery has been associated with better quality of life and functional status. 17 However, the potential utility of risk-standardized home time as a hospital-level performance metric for cardiac surgery is not well established. Accordingly, this study aimed to evaluate the association of 90-day risk-standardized home time with other measures of hospital performance and long-term outcomes.…”
mentioning
confidence: 99%
“…32 Greater time spent at home during postsurgical recovery has been previously associated with higher quality of life in a broad surgical study. 33 For patients with hearing disabilities, telemedicine during the pandemic may improve patients' comprehension since masks prevent them from "reading the lips" of clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…48 Nonetheless, personal preferences should be considered when making arrangements for postsurgical care since some older patients, particularly those who live alone or have special medical needs, may value time recovering at a rehabilitation facility. 49 We found that nonelective surgery was significantly associated with days away from home in bivariate but not multivariable analyses. This is likely due to large differences in *Identified from the final zero-inflated negative binomial model that included all 394 observations.…”
Section: Discussionmentioning
confidence: 61%